2018
DOI: 10.3390/ma11061015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cutting Edge Microgeometry on Residual Stress in Orthogonal Cutting of Inconel 718 by FEM

Abstract: Service performance of components such as fatigue life are dramatically influenced by the machined surface and subsurface residual stresses. This paper aims at achieving a better understanding of the influence of cutting edge microgeometry on machined surface residual stresses during orthogonal dry cutting of Inconel 718. Numerical and experimental investigations have been conducted in this research. The cutting edge microgeometry factors of average cutting edge radius trueS¯, form-factor K, and chamfer were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The distribution trend of residual stress along the negative Y-axis in the turned shallow surface is approximately hook-shaped for Inconel 718 material [ 26 ], as exhibited in Figure 3 a. The cutting process is coupled with thermal-mechanical loads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution trend of residual stress along the negative Y-axis in the turned shallow surface is approximately hook-shaped for Inconel 718 material [ 26 ], as exhibited in Figure 3 a. The cutting process is coupled with thermal-mechanical loads.…”
Section: Methodsmentioning
confidence: 99%
“… ( a ) The hook-shaped tendency of residual stress in the shallow surface [ 26 ]. ( b ) The cutting forces in the turning simulations.…”
Section: Figurementioning
confidence: 99%
“…The effect of the tool material and edge preparation had the greatest percentage contribution to flank wear [20]. Qi Shen et al [21] investigated the effect of cutting edge microgeometry on residual stresses by FEM. The results from the numerical experiment stated that an increase in the size of the cutting edge radius caused enhanced values of the surface tensile residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…Using the experimental and numerical investigation, Madariaga et al [22] reported that tool wear remarkably changes surface residual stress in face turning of Inconel 718. The influence of cutting edge geometry was numerically investigated in 2D modeling of Inconel 718 cutting by Shen et al [23]. They found that more tensile residual stresses are induced in superficial layers, when chamfered tool is used.…”
Section: Introductionmentioning
confidence: 99%